WORKSHOP BEDAH PANDUAN PENGEMBANGAN PENDIDIKAN INKLUSIF UNESCO BAGI AKTOR PENDIDIKAN DI PROVINSI NTB - Lalu Hamdian Affandi; Arif Widodo; Asri Fauzi; Vivi Rachmatul Hidayati (SELAPARANG Jurnal Pengabdian Masyarakat Berkemajuan, 2022)
ABSTRAKPendidikan inklusif di provinsi NTB telah lama didengungkan. Namun demikian dalam implementasinya di sekolah pendidikan inklusif masih banyak mengalami hambatan. Implikasinya adalah perkembangan pendidikan inklusif di NTB masih jauh dari harapan. Salah satu hambatan yang dijumpai adalah tidak adanya panduan praktis dalam pengembangan implementasi pendidikan inklusif di sekolah. UNESCO sebagai salah satu lembaga dunia yang menaruh perhatian besar terhadap pendidikan inklusif telah menerbitkan panduan pengembangan pendidikan inklusif di sekolah. Pada dasarnya panduan tersebut telah disusun secara sistematis, namun demikian panduan tersebut terlalu kompleks sehingga perlu disederhanakan dan disesuaikan dengan kondisi sekolah di NTB. Kegiatan ini bertujuan untuk memberikan pelatihan kepada aktor pendidikan dalam menyusun panduan penyelenggaraan pendidikan inklusif. Sasaran kegiatan ini adalah para aktor pendidikan di provinsi NTB yang terdiri dari unsur pemerintah, perguruan tinggi, NGO dan sekolah penyelenggara pendidikan inklusif. Melalui workshop ini diharapkan dapat tersusun draf panduan pengembangan pendidikan inklusif yang lebih sederhana sehingga mudah diterapkan dalam penyelenggaraan pendidikan inklusif di sekolah. Alur kegiatan dilakukan dengan tahapan ICARE (Introduction, Connection, Application, Reflection, dan Extension). Hasil akhir kegiatan didapatkan tiga draf panduan pengembangan pendidikan inklusif di sekolah, antara lain draf pengembangan sekolah inklusif unggulan, draf panduan pengembangan pendidikan inklusif dalam pembelajaran dan draf panduan pelibatan mitra dalam pendidikan inklusif. Kata kunci: panduan pengembangan; pendidikan inklusif; aktor pendidikan. ABSTRACTInclusive education in the province of NTB has long been touted. However, in its implementation in schools, inclusive education still faces many obstacles. The implication is that the development of inclusive education in NTB is still far from expectations. One of the obstacles encountered is the absence of practical guidelines in developing the implementation of inclusive education in schools. UNESCO as one of the world institutions that pay great attention to inclusive education has published guidelines for the development of inclusive education in schools. These guidelines have been compiled systematically, however, these guidelines are too complex and need to be simplified and adapted to the conditions of schools in NTB. Based on these problems, it is necessary to hold community service activities with the theme of workshops on the preparation of guidelines for the development of inclusive education based on guidelines that have been published by UNESCO. The target of this activity is education actors in the province of NTB consisting of elements of the government, universities, non-governmental organizations, and schools providing inclusive education. Through this workshop, it is hoped that a simpler draft guide for the development of inclusive education can be drawn up so that it is easy to implement in the implementation of inclusive education in schools. The flow of activities is carried out in ICARE stages (Introduction, Connection, Application, Reflection, and Extension). The final results of the activity obtained three drafts of guidelines for developing inclusive education in schools, including a draft of developing inclusive schools, a draft of a guide for developing inclusive education in learning, and a draft of a guide for involving partners in inclusive education. Keywords: development guide; inclusive education; education actor.